3, 14‐Bis(p‐nitrophenyl)‐17, 17‐dipentyltetrabenzo[a, c, g, i]‐fluorene: A New Fluorophore Displaying Both Remarkable Solvatochromism and Crystalline‐Induced Emission. Issue 2 (13th December 2012) - Ueda, Yoshiaki; Tanigawa, Yusuke; Kitamura, Chitoshi; Ikeda, Hiroshi; Yoshimoto, Yuichi; Tanaka, Mirai; Mizuno, Kazuhiko; Kurata, Hiroyuki; Kawase, Takeshi
Abstract A series of 17, 17‐dialkyl‐3, 14‐diaryltetrabenzofluorenes were efficiently prepared by using Suzuki–Miyaura cross‐coupling reactions of the corresponding 3, 14‐dibromo derivatives. Studies of the unique fluorescence properties of these compounds showed that they display intense blue to yellow fluorescence with high quantum yields in the solution state and blue to orange fluorescence with moderate quantum yields in the solid state. In addition, the fluorescence wavelength of the bis(p‐nitrophenyl) derivative is remarkably solvent‐dependent in a manner that correlates with the solvent polarity parameter ET(30). The results of density function theory calculations suggest that the intramolecular charge‐transfer character of the HOMO–LUMO transition is responsible for the large solvent effect. Moreover, addition of water to a tetrahydrofuran (THF) solution of this compound leads to quenching of the yellow fluorescence owing to an increase in the solvent polarity. However, when the amount of water fraction exceeds 70 %, a new fluorescence band appears at the same orange‐red emission wavelength as that of the solid‐state fluorescence. This observation suggests the occurrence of a crystallization‐induced emission (CIE) phenomenon in highly aqueous THF.